(untitled) (Research, Society and Development, 2022)
Salinity is one of the abiotic effects that most harm the growth and development of crops. Lettuce is considered moderately sensitive to altered salinity in its production when such conditions change. In this sense, the objective was to evaluate the morphophysiological and yield characteristics of two lettuce cultivars under different irrigation water salinity levels. The Pernambuco Experience Unit at the Federal Rural University of Maio (UFRPE), in Serra Talhada - PE. The experimental design used was completely randomized in a 2 x 4 factorial scheme, with six replications, totaling 48 experimental units. Treatments resulted from two lettuce cultivars (Folha Roxa Quatro Estações and Grandes Lagos Americanas) with four irrigation water salinity levels (N1-0.0; N2-0.9; N3-1.2 and N4- 3.0 dS m-1). Product levels were obtained by Cl. Biometric, productivity and physiochemical analyzes were performed. The cultivar Roxa Quatro Estações presented a greater number of live and total leaves and stem diameter. Both similar varieties are similar when they can be grown with saline water.